Dormant carbohydrate reserves enhance pecan tree spring freeze tolerance: controlled environment observations - Kaur, Amandeep; Zhang, Lu; Maness, Niels O.; Ferguson, Louise; Graham, Charles J.; Sun, Yanwei; Panta, Srijana; Pokhrel, Niranjan; Yang, Ming; Moss, Justin Q. (Frontiers in Plant Science, 2024)
Pecan (Carya illinoensis), an economically important deciduous tree, bears commercially valuable nutritional nuts. Spring freezes in April can severely injure pecan buds, decreasing bloom, and fruit set. This study determined how low temperatures affect pecan buds/flowers at different growth stages in several pecan scion/rootstock combinations. This study focused on three pecan scion/rootstock combinations: Pawnee/Peruque (PP), Kanza/Giles (KG), and Maramec/Colby (MC), grown at the Cimarron Valley Research Station, Perkins, Oklahoma. Branches at three different growth stages, i.e., outer bud scale shed, one week after bud break, and early bloom stages were collected from PP, MC, and KG. Branches were held in a Conviron E8 freezing unit at 4 temperatures (-2, 0, 2, and 4°C) for 4 and 8 hours; A total of 8 treatments. One sample set was kept as an untreated control. After 2-3 weeks, branch samples from all the temperature treatments were observed and categorized into two groups. Group one with number of branches had healthy buds/formation of healthy leaves/flowers and group two with number of dead branches. The carbohydrate content reserved from dormant was analyzed using an Anthrone reagent. Visual observations and carbohydrate analyses revealed differences in damage and carbohydrate content among the scion/rootstock combinations, low-temperature treatments, and growth stages. The MC combination had minimum visual damage to leaves, buds, and flowers and significantly lower soluble sugars and starch in bark phloem as well as significantly lower soluble sugars in woody 2 tissue xylem. The KG combination had maximum visual damage and significantly higher soluble sugars and starches in the bark, and soluble sugars in the woody tissues. These results indicate the MC combination is more tolerant to spring freeze damage at all three growth stages compared to the other two pecan scion/rootstock combinations. The results also demonstrate the MC combination is using more non-structural carbohydrates, soluble sugars and starches, suggesting this is a possible mechanism in its freeze tolerance.